PIERRE BOURDIEU, LANGUAGE AND SYMBOLIC POWER - Eka Ningtyas (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Judul: Language and Symbolic PowerPenulis: Pierre BourdieuPenerbit: Polity Press, MaldenTahun: 2007Tebal: 302 halaman